Pharmacotherapy of Behavioral and Psychological Symptoms of Dementia: State of the Art and Future Progress - Magierski, Radoslaw; Sobow, Tomasz; Schwertner, Emilia; Religa, Dorota (Frontiers in Pharmacology, 2020)
Behavioural and psychological symptoms of dementia (BPSD) or neuropsychiatric symptoms (NPS) are core symptoms of different dementia subtypes. In the case of dementia due to Alzheimer's disease (AD), BPSD symptoms may occur at any stage of the disease, whereas in the behavioural variant frontotemporal dementia, or dementia with Lewy bodies they are early and essential for diagnosis. BPSD treatment consists of non-pharmacological as well as pharmacological interventions, with non-pharmacological interactions being suggested as the first-line treatment. Agitation, psychotic features, apathy, depression, and anxiety may not respond to acetylcholinesterase inhibitors or memantine in AD cases, so prescription of antipsychotics, antidepressants, sedative drugs or anxiolytics, and antiepileptic drugs is practiced. Hypersensitivity to antipsychotic drugs in observed in DLB cases and lack of effective pro-cognitive treatment in frontotemporal dementia further complicates the management of BPSD. Aim of the paper is to review current knowledge, limitations and practices in the management of BPSD and to discuss on-going clinical trials and therapeutic options being on the horizon.